2000
DOI: 10.1136/thorax.55.9.789
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in physician diagnosed COPD in women and men in the UK

Abstract: Background-Recent trends in physician diagnosed chronic obstructive pulmonary disease (COPD) in the UK were estimated, with a particular focus on women. Methods-A retrospective cohort of British patients with COPD was constructed from the General Practice Research Database (GPRD), a large automated database of UK general practice data. Prevalence and all-cause mortality rates by sex, calendar year, and severity of COPD, based on treatment only, were estimated from January 1990 to December 1997. Results-A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
150
3
18

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(182 citation statements)
references
References 17 publications
11
150
3
18
Order By: Relevance
“…22 Prevalence rates at the beginning of the study period in 2001 (female: 1.3%; male 1.5%) were also very similar to those found in 1997 using the UK General Practice Research Database (female 1.4%; male 1.6%). 4 Higher rates of COPD diagnosed in primary care in northern England and deprived communities found in the present study have also been previously reported. 23 Mean consultation rates (7.9 per year) were higher than those from a survey conducted in 2002 of 500 patients throughout the UK with COPD (6.6 visits per year), although this was a telephone survey that relied on patient recollection and may have been affected by recall bias.…”
Section: Comparison With Existing Literaturesupporting
confidence: 74%
See 1 more Smart Citation
“…22 Prevalence rates at the beginning of the study period in 2001 (female: 1.3%; male 1.5%) were also very similar to those found in 1997 using the UK General Practice Research Database (female 1.4%; male 1.6%). 4 Higher rates of COPD diagnosed in primary care in northern England and deprived communities found in the present study have also been previously reported. 23 Mean consultation rates (7.9 per year) were higher than those from a survey conducted in 2002 of 500 patients throughout the UK with COPD (6.6 visits per year), although this was a telephone survey that relied on patient recollection and may have been affected by recall bias.…”
Section: Comparison With Existing Literaturesupporting
confidence: 74%
“…It was hypothesised that this sex disparity resulted from the rising prevalence of smoking among women in the 1980s and 1990s and the longstanding plateau in smoking cessation among men. 4 The prevention of smoking and the promotion of smoking cessation services are the main strategies to prevent the occurrence and reduce the burden of COPD. In this vein, it is likely that the 2004 Public Service Agreement in England objectives of reducing overall adult smoking rates from 26% to 21% or less by 2010 5 are likely to be surpassed.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both lung cancer and COPD have been previously studied in the GPRD and the findings reported. [13][14][15][16][18][19][20][21] Indeed, the higher risk of lung cancer we found among those with COPD aged 65 or older has also been reported elsewhere. 29 In a large, recent study, Wilson et al, 31 using CT scan together with spirometry to search for emphysema and lung cancer in 3,638 smokers, were intrigued to find absence of a doseresponse relationship between smoking intensity and lung cancer among those with moderate to severe emphysema -a finding which has led to the hypothesis that COPD patients may have some host or susceptibility factors that protect them from developing cancer in general (having taken 30 or more years of exposure to tobacco to develop COPD), whereas in those who are more susceptible to developing cancer, lung cancer is likely to be diagnosed before COPD.…”
Section: Discussionsupporting
confidence: 57%
“…A growing number of studies conducted in the GPRD database have been widely reported elsewhere, and the GPRD update as of December 2006 was used in this study. [18][19][20][21] This study was conducted within a research protocol approved by the Independent Scientific Advisory Committee (ISAC) of the GPRD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation